Innovative technologies for reverse total shoulder arthroplasty in Australia: Market access challenges and implications for patients, decision-makers, and manufacturers - Mutsa Gumbie; Michelle Costa; Michael Erb; Gnanadarsha Dissanayake (Taylor & Francis Group, 2023)
ABSTRACTPurpose The success of reverse total shoulder arthroplasty (RTSA) has expanded its use for a broader range of shoulder indications worldwide. Evidence regarding the relative efficacy and long-term safety of medical technologies used in RTSA is subjected to rigorous assessment. Nonetheless, substantial challenges impede market access for innovative shoulder implant technologies for RTSA in Australia, resulting in delayed patient access.Approach This paper addresses the key challenges associated with generating evidence for the health technology assessments of innovative medical technologies for RTSA that are required for access to the Australian market. The transition to value-based care requires establishing a benchmarking reference that incorporates patient-reported outcome measures (PROMs) and combines revision outcomes with additional clinical outcomes to increase patient cohort sizes. Establishing the benchmark would require agreement on the outcome measures to be collected for each indication, and investment in reporting patient-reported outcomes for RTSA to the national orthopaedic registry.Implications for practice The need for increased flexibility in developing evidence for health technology assessment of RTSA medical technologies is required. Optimised approaches for benchmarking RTSA require extensive stakeholder discussions, including the agreement on evidence requirements and follow-up periods, selection of clinical outcomes, as well as pre-operative and post-operative PROMs as a value assessment.